Hubungan Dukungan Suami dengan Keikutsertaan Akseptor KB IUD - Muhammad Hasan Azhari; Siska Delvia (Universitas Respati Indonesia, 2025)
Anemia in pregnant women in the third trimester remains a health problem that can increase the likelihood of complications during pregnancy and childbirth. One preventive measure for anemia is to comply with the recommended consumption of Fe tablets. This study aims to analyze the relationship between adherence to consuming Fe tablets and the occurrence of anemia in pregnant women in the third trimester at TPMB Bdn. Titik Aryanti, S. Keb. This type of research is analytical with a cross-sectional design. The study subjects included all pregnant women in the third trimester who underwent examination at TPMB Bdn. Titik Aryanti, S. Keb with a total sample of 37 participants, selected using the total sampling method. Information on adherence to consuming Fe tablets was collected through questionnaires, while data on anemia were obtained from hemoglobin level examinations. Data analysis was performed using statistical tests. The findings of this study indicate a significant relationship between adherence to consuming Fe tablets and the incidence of anemia in pregnant women in the third trimester with a p value of 0.034 (p < 0.05). The conclusion of this study is that there is a meaningful relationship between adherence to consuming Fe tablets and the incidence of anemia in pregnant women in the third trimester. It is hoped that health workers can improve education and monitoring of compliance in consuming Fe tablets for pregnant women